IMPLEMENTASI PENGAPLIKASIAN POINT OF SALES (POS) UNTUK PENGELOLAAN SISTEM INFORMASI PADA TOKO NURFALAH KABUPATEN LOMBOK TIMUR - Nia Kurniati; Nasruddin Nasruddin (Nusantara Hasana Berdikari, 2021)
Along with the development of information technology, the recording of transaction systems in retail trade is very necessary. However, there are still shops/retails that still use the conventional system in every transaction. This of course affects the performance of the store, especially in providing services to consumers. In addition, various required information such as stock of goods and financial reports cannot be obtained accurately. This activity aims to provide training and assistance to Nurfalah Store management in using the POS system for all forms of transactions such as inputting goods, stocking goods, selling and purchasing transactions, financial reports, and various other transactions related to the presentation of store information. The stages of the method used in this service are the preparation stage and the activity implementation stage. In the preparatory stage carried out are site surveys, problem identification, providing simulations of the use of POS to partners. The stages of implementing the activities include the installation of a POS system, training and mentoring, evaluation and reporting of service. The result of this activity is that the application of the POS system is able to provide better service to consumers, because consumers can get shopping receipts. In addition, reports on the presentation of data on goods, stock of goods, sales and purchase transactions, financial reports can be accessed quickly, precisely and accurately when compared to using a manual system.